2022
DOI: 10.1021/acs.macromol.1c02029
|View full text |Cite
|
Sign up to set email alerts
|

Study of Linear and Cyclic Graft Polystyrenes with Identical Backbone Contour in Dilute Solutions: Preparation, Characterization, and Conformational Properties

Abstract: Exploring the difference in the topology−structure−conformation relationship for linear and cyclic graft polymers is an interesting topic. In this work, two libraries of linear graft (l-PPA-g-PS, with a linear backbone) and cyclic graft (c-PPAg-PS, with a cyclic backbone) polystyrenes with low ratios of the backbone-to-sidechain contour length (r c , from 1.26 to 6.22) and various grafting densities (σ, from 0.16 to 0.86) have been studied as models. Atomic force microscopy (AFM) characterization has indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…As shown in Figure (dashed lines), after cyclization, the SEC peak is obviously shifted to a higher elution time ( t e ). The ratio of peak molar masses of the cyclic product ( M p, c ) to the linear precursor ( M p, l ), i.e., M p, c / M p, l , is found to be from 0.75 to 0.76, which is consistent with the values reported in the literature. , MALDI-TOF-MS is employed to further confirm the highly efficient cyclization reaction (Figure S1). The interpretation of data in relevant spectra is given in the Supporting Information.…”
Section: Resultssupporting
confidence: 88%
“…As shown in Figure (dashed lines), after cyclization, the SEC peak is obviously shifted to a higher elution time ( t e ). The ratio of peak molar masses of the cyclic product ( M p, c ) to the linear precursor ( M p, l ), i.e., M p, c / M p, l , is found to be from 0.75 to 0.76, which is consistent with the values reported in the literature. , MALDI-TOF-MS is employed to further confirm the highly efficient cyclization reaction (Figure S1). The interpretation of data in relevant spectra is given in the Supporting Information.…”
Section: Resultssupporting
confidence: 88%
“…One can see that the backbones of the linear BBPs become more rigid upon increasing the PEO side-chain length, consistent with many previous studies. , For cyclic BBPs, the backbone also becomes more elongated, but the overall structure remains more compact compared to the linear counterpart. Previous experiments have shown that cyclic BBPs are more compact and assume a smaller hydrodynamics volume than the corresponding linear ones . To quantitatively compare the range of conformations that bottlebrushes explore, we calculated the frequency distribution of the radius of gyration ( R g ) of the cyclic and linear BBPs, shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Experiments have established that the difference in backbone topology results in different molecular properties, e.g., cyclic BBPs exhibit a more compact shape and less interchain association , than their linear analogues. Although experiments , and dissipative particle dynamics simulations have elucidated many macroscopic properties of cyclic BBPs such as viscosity and self-assembled structures, the molecular-level details of structure and dynamics are still missing. Obviously, it would be informative to investigate the similarities and differences in the conformational behavior and properties of cyclic and linear BBPs in order to achieve a fundamental understanding of the chain topology effect.…”
Section: Introductionmentioning
confidence: 99%
“…The detail of synthesis is summarized in the Supporting Information (pages S2–S5). In fact, the esterification of PAA by the TMG method has been widely proven very efficient even under the condition of stoichiometric ratio. In our study, the sufficient reaction time and much excess of TMG and benzyl bromide can ensure the complete conversion of AA into the ester group. A set of PBA samples with different molar masses have been prepared (Figure a).…”
Section: Resultsmentioning
confidence: 78%